Visibal management and its implications for Organizational culture A survey of a sample of R & D staff / Ministry of Higher Education and Scientific Research - سعيد, هدى قاسم (Journal of Economics and Administrative Sciences, 2018)
The research aims to shed light on the concept of Visibal management and its reflection on the organizational culture of the organization. The visual administration is a modern administrative method that contributes to the renewal and development of the organization's reality through surveying the opinions of a sample of 61 employees in the R & D / Ministry of Higher Education and Scientific Research. (130) individuals. The questionnaire was used as a main tool for collecting data and information, and their answers were analyzed using the SPSS program in data entry and analysis. The most important tools are computational circles, standard deviations, method of analysis and regression equation. There is a possibility to apply the visual management method in the R & D department according to its administrative and technical requirements through the results of the average responses of the sample on the main and secondary research variables. The visual administration affects its administrative and technical requirements in the elements of organizational culture represented in Visibal, beliefs, (Regulatory requirements, organizational beliefs, organizational norms, organizational expectations). Employees are aware that drawing up a set of strategic plans in departmental departments is a priority for administrative work and a basic requirement of Visibal management. The study recommends removing all obstacles that undermine the possibility of applying the administrative and technical requirements of visual management by spreading the culture of visual management and making it compatible with the Visibal, beliefs, norms and organizational expectations in the R & D department, and establishing appropriate mechanisms to reward outstanding employees and fairness.